2013
DOI: 10.4018/jitpm.2013070104
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Risk of Construction Projects Delays in the UAE

Abstract: The growing rate of delays in project delivery is considered a major criticism of the construction companies in the United Arab Emirates (UAE). This paper aims to investigate the causes and effects behind the delays pertaining to delivery of construction projects in the UAE. The study is exploratory in nature, and incorporates a pilot questionnaire survey and interviews. An extensive literature review indicates potential factors that have possible effects on construction completion delay. The questionnaire for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Kazaz, Ulubeyli and Tuncbilekli (2012) examined various causes of time delay in the context of Turkish construction industry and the levels of their significance, design and material changes, delay of payments and cash flow problems are the most predominant delay factors in Turkish construction industry. Motaleb and Kishk (2013) examined problems causing delays on construction projects in the United Arab Emirates; they investigated the causes and effects behind the delays that pertain to the delivery of construction projects in the United Arab Emirates, they identified and ranked the most key factors as follows: Change orders, Inadequate capabilities of client delegate, Delay in decision making by client delegate, Poor experience of client in construction, Insufficient management and supervision, Lack of experience of project team, Inflation/prices fluctuation, Poor time estimating, Construction materials delivery related problems, Improper project planning / scheduling, Imprecise cost estimating, High bank interest rate, Client's poor financial statement, Extravagant restriction to client ,Improper construction methods. Elawi et al (2016) investigated the reasons of the time delay in infrastructure projects in the Mecca province in Saudi Arabia.…”
Section: Critical Delays Reviewmentioning
confidence: 99%
“…Kazaz, Ulubeyli and Tuncbilekli (2012) examined various causes of time delay in the context of Turkish construction industry and the levels of their significance, design and material changes, delay of payments and cash flow problems are the most predominant delay factors in Turkish construction industry. Motaleb and Kishk (2013) examined problems causing delays on construction projects in the United Arab Emirates; they investigated the causes and effects behind the delays that pertain to the delivery of construction projects in the United Arab Emirates, they identified and ranked the most key factors as follows: Change orders, Inadequate capabilities of client delegate, Delay in decision making by client delegate, Poor experience of client in construction, Insufficient management and supervision, Lack of experience of project team, Inflation/prices fluctuation, Poor time estimating, Construction materials delivery related problems, Improper project planning / scheduling, Imprecise cost estimating, High bank interest rate, Client's poor financial statement, Extravagant restriction to client ,Improper construction methods. Elawi et al (2016) investigated the reasons of the time delay in infrastructure projects in the Mecca province in Saudi Arabia.…”
Section: Critical Delays Reviewmentioning
confidence: 99%
“…Financial difficulties of the contractors, managerial problem, and manpower related issues (i.e. lack of labors or unqualified labors) are also significant factors of construction delay in UAE [33,34]. Construction projects in Iraq are not delivered on time owing to contractor's lack of experience, delay in progress payment by owner, frequent change order, design error, and lowest bidder selection [35].…”
Section: Amentioning
confidence: 99%
“…It has been observed that the delays in WICPs in the Abu Dhabi Emirate have increased considerably in the last ten years and the government, at present, is spending billions of dollars, and it is expected that more money will be invested in this sector. Occasionally, new difficulties develop, and, despite the serious efforts to put into action every success measure, these problems persist (Motaleb & Kishk, 2013). Similar problems are notified in the status of numerous WICPs.…”
Section: Justification For the Studymentioning
confidence: 91%
“…The problems facing the construction industry have a negative impact on construction projects, in general, and, ultimately, affect the economy as a whole (Motaleb & Kishk, 2013). Hence, this research investigates these problems in the context of water infrastructure projects in the Abu Dhabi Emirate in order to highlight the importance of the success factors that could avoid or eradicate the delay factors that affect WICPs in the Abu Dhabi Emirate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation